The New Industrial Job: A Critical Analysis from the Quality of the Job - Rodríguez Miglio, Martín; Erbes, Analía; Roitter, Sonia; Pujol, Andrea (Sociedad y Economía, 2015)
In this article we address the relationship between new ways of organizing production and job quality. In doing this, we critically review the most traditional perspectives. Par- ticularly, we examine the scope of the impact on job quality when adopting new ways of production structure. In doing this, changes made during the working process from the beginning of capitalism are analyzed, focusing on the changes that occurred during the last quarter of the 20th Century. Some of the key findings point out that changes in the factors that shape productive organization and labor management have a questionable impact on job quality and workers’ welfare